Pengaruh Komunikasi Efektif Untuk Meningkatkan Hasil Belajar Mahasiswa - Hugo Aries Suprapto (Khazanah Pendidikan, 2017)
AbstractWith effective communication, the managerial functions that originated from thefunctions, implementation and monitoring can be achieved. This study used anexperimental method. Subjects were students of the seventh semester of IndustrialEngineering as many as 25. There is a significant influence effective communication toincrease student learning outcomes. The data was processed with SPSS 22. The resultsshowed, normality test, homogeneity and T Samples Paired with a significant level of α= 5%, the normality test results obtained prior to the effective communicationKolmogorof-Smirnov value Sig. 0190, and Shapiro-Wilk 0215 so that at α = 5% = 0:05<Sig. = 0, the sample data came from a normal distribution. While the test results ofnormality after the effective communication of values obtained Kolmogorof-SmirnovSig. 0134, and Shapiro-Wilk 0346 so that at α = 5% = 0:05 <Sig. = 0, the sample datacame from a normal distribution. At Variance Homogeneity Test Levene Value Sig.0096, at a significance level of α = 5% = 0:05 <Sig.0.096 so that it can be said of datasamples derived from the variances are homogenous, it can be concluded on aconfidence level of 95%, on average after the effective communication to improvestudent results mean for entrepreneurship courses 80.9600) compared to before usingeffective communication (mean of 64.7200), rose by 16:24. In other words, the use ofeffective communication wear a significant effect on improving learning outcomes95%. This study gives suggestions to overcome the problems found in the study.Keywords: effective communication, learning outcomes